2015
DOI: 10.1016/j.physb.2015.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Phase coherence and spectral functions in the two-dimensional excitonic systems

Abstract: a b s t r a c tThe nonlocal correlation mechanism between excitonic pairs is considered for a two dimensional exciton system. On the base of the unitary decomposition of the usual electron operator, we include the electron phase degrees of freedom into the problem of interacting excitons. Applying the path integral formalism, we treat the excitonic insulator state (EI) and the Bose-Einstein condensation (BEC) of preformed excitonic pairs as two independent problems. For the BEC of excitons the phase field vari… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…This effort was motivated by physical, but also practical reasons, as the existence of ferroelectrics based on the purely electronic mechanism would provide a new set of physical properties and technological applications, as for example, the possibilities of controlling optical properties of materials with magnetic fields. Since the Falicov-Kimball model (FKM) is probably the simplest model of electronic phase transitions in rare-earth and transition-metal compounds [9], it was natural to test the idea of electronic ferroelectricity [10][11][12][13][14][15][16][17][18][19][20][21], which is directly related with formation of excitonic insulator [22][23][24][25][26][27][28][29][30][31][32][33][34][35], just on this model and its extensions.…”
Section: Introductionmentioning
confidence: 99%
“…This effort was motivated by physical, but also practical reasons, as the existence of ferroelectrics based on the purely electronic mechanism would provide a new set of physical properties and technological applications, as for example, the possibilities of controlling optical properties of materials with magnetic fields. Since the Falicov-Kimball model (FKM) is probably the simplest model of electronic phase transitions in rare-earth and transition-metal compounds [9], it was natural to test the idea of electronic ferroelectricity [10][11][12][13][14][15][16][17][18][19][20][21], which is directly related with formation of excitonic insulator [22][23][24][25][26][27][28][29][30][31][32][33][34][35], just on this model and its extensions.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, it has been shown [19,20] that the single-particle coherent density of states (DOS) in the usual two-dimensional (2D) [19] and three-dimensional (3D) [20] semiconducting systems at the zero temperature limit is always finite, reflecting with the excitonic condensate regime in these systems. For the 3D semiconducting systems, the coherent DOS spectra survive also for the higher temperatures [20].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been shown that there exists a critical value of the interlayer hopping amplitude γ 1 [15], which provides an interesting energy cutoff, below which the electron-hole correlations do not drive the system towards the CSB excitonic transition. More recently, it has been shown [19,20] that the single-particle coherent density of states (DOS) in the usual two-dimensional (2D) [19] and three-dimensional (3D) [20] semiconducting systems at the zero temperature limit is always finite, reflecting with the excitonic condensate regime in these systems. For the 3D semiconducting systems, the coherent DOS spectra survive also for the higher temperatures [20].…”
Section: Introductionmentioning
confidence: 99%